Peritoneal expression of SGLT-2, GLUT1 and GLUT3 in peritoneal dialysis patients - Severin Schricker; Tina Oberacker; Peter Fritz; Markus Ketteler; Mark Dominik Alscher; Moritz Schanz (Karger Publishers, 2021)
Introduction: In peritoneal dialysis (PD) patients, the peritoneal membrane is affected by glucose-based solutions used as peritoneal dialysate fluids. This exposure leads to changes of the membrane which may eventually culminate in fibrosis and method failure. In vitro or animal studies demonstrated that glucose transporters are upregulated upon exposure to these solutions. Expression studies of glucose transporters in human peritoneum have not been reported yet. Methods: Expression of SGLT-2, GLUT1, and GLUT3 in human peritoneal biopsies was analysed by real-time polymerase chain reaction (qPCR) and Western blot analysis. The localization of these glucose transporters in the peritoneum was evaluated by immunohistochemistry using a Histo-Score. Results: Peritoneal biopsies of patients (healthy controls, uremic, PD and encapsulating peritoneal sclerosis (EPS)) were analyzed. We found evidence of SGLT-2, GLUT1 and GLUT3 expression in the peritoneal membrane. Protein expression of SGLT-2 increases with PD-duration and is significantly enhanced in EPS patients. All transporters were predominantly, but not exclusively, located adjacent to the vessel walls of the peritoneal membrane. Conclusion: Our study showed that SGLT-2, GLUT1 and GLUT3 were regularly expressed in the human peritoneum. SGLT-2 was particularly upregulated in PD patients with EPS, suggesting that this upregulation may be associated with pathological changes in the peritoneal membrane in this syndrome. Since preclinical studies in mice show that SGLT-2 inhibitors or downregulation of SGLT-2 ameliorated pathological changes in the peritoneum, SGLT-2 inhibitors may be potentially promising agents for therapy in PD patients that could reduce glucose absorption and delay functional deterioration of the peritoneal membrane in the long-term.